Estudo das propriedades vibracionais de titanatos lamelares - Fábio Lacerda Resende e Silva (2017)
Titanium oxides with lamellar structure have been shown to be important materials for technological applications. There are many papers concerning in the use of these materials in photocatalysis, batteries, sensors, dye adsorption and, others. Despite these advanced studies in applications, some fundamental physical properties of layered titanates are still under debate. In this work, the vibrational properties of layered titanates with different morphologies, crystalline structures and compositions were performed by Raman and infrared spectroscopy techniques. The Na2Ti3O7 and Na2Ti6O13 bulk samples were produced by solid-state reaction of titanium dioxide and sodium carbonate. Polarized Raman spectroscopy measurements were performed in isolated microcrystals, which allowed the assignment of the phonons symmetry. A detailed analysis of the vibrational modes of these samples was performed by comparing the experimental Raman and infrared (IR) results with first-principles calculations within the framework of density functional theory. Besides these two samples, sodium and potassium nanoribbons were produced by hydrothermal treatment from titanium dioxide in an alkaline solution of sodium hydroxide and potassium hydroxide, respectively. These nanoribbons were treated in a hydrochloric acid solution to promote the sodium and potassium proton exchange. The morphology of the nanoribbons was investigated by electron microscopy images. Measurements of atomic absorption (AAS) and energy dispersive (EDS) spectroscopies revealed that the potassium nanoribbons have a less ion exchange capacity than the sodium nanoribbons. This behavior can be related with the tunnel-like structure of potassium nanoribbons. The dependence between the lattice parameters and sodium/potassium quantities were obtained by X ray diffraction (XRD) data analysis. The zone axis and crystal growth direction were determined by selected area electron diffraction (SAED). The influence of the ion exchange in the vibrational properties of these samples was investigated by Raman and infrared spectroscopy techniques. Titanate nanotubes decorated with cobalt ferrite nanoparticles have been prepared by a two-step synthesis process. Firstly, nanoparticles of CoFe2O4 were prepared by the coprecipitation method and added to a NaOH aqueous solution with titanium dioxide. In the next step, the mixture was hydrothermally treated yielding in the studied material. This sample showed good results in adsorption of Basic Green 1 dye (BG1) in aqueous solution, revealing that our sample is a very promising material for wastewater treatment.